Micro-variazione dell’accordo con soggetti post-verbali: Spunti di riflessione sui dati raccolti in due inchieste nel Trentino meridionale - Cordin, Patrizia (Verbum – Analecta Neolatina, 2025)
This work aims to describe the micro-variation in the sentences with post-verbal subjects in the dialectal varieties of southern Trentino. Like many other northern Italian varieties, the dialects of this area possess subject clitics, which appear in proclitic position in declarative constructions with a pre-verbal third-person subject and usually do not appear in sentences where the subject follows the verb. Thanks to a field survey and an online collection of oral data, it has been possible to observe the micro-variation present in the area, where numerous realizations deviate from the structure described as canonical for verb-subject (VS) order sentences. This work highlights those elements that induce speakers to produce VS constructions with the clitic that realizes verbal agreement. Furthermore, the comparison between the data collected in the two surveys, the field one and the online one, shows that only a high number of data points allows for the capture of aspects that provide a comprehensive view of the phenomenon in question.